2011
DOI: 10.1007/s10156-010-0166-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of doripenem (DRPM) against Pseudomonas aeruginosa in murine chronic respiratory tract infection model

Abstract: Doripenem is a carbapenem antibiotic with broad-spectrum coverage of gram-positive and gram-negative bacteria, including Pseudomonas aeruginosa, and is considered to be as effective as meropenem. The in vivo activity of doripenem was thus compared with that of meropenem in a chronic lower respiratory P. aeruginosa infection mouse model. The number of viable bacteria in the lungs after treatment with doripenem, meropenem, and saline mice was 2.01 ± 0.69, 2.03 ± 0.48 and 3.90 ± 1.40 log 10 CFU/lung, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been suggested that the expression of MexA-MexBOprM might be down-regulated when the peripheral environment is permissive to bacterial growth and survival (21). Thus, silencing of MexB gene expression was considered a promising mechanism by which antibiotic sensitivity could be induced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the expression of MexA-MexBOprM might be down-regulated when the peripheral environment is permissive to bacterial growth and survival (21). Thus, silencing of MexB gene expression was considered a promising mechanism by which antibiotic sensitivity could be induced.…”
Section: Discussionmentioning
confidence: 99%